L'amministrazione dei culti in Francia (Stato, Chiese e pluralismo confessionale, 2013)
Contributo sottoposto a valutazioneSOMMARIO: 1. Introduzione - 2. La Francia e l’amministrazione dei culti - 3. Le bureau central des cultes: 3.1 - Le origini: dal Consolato al periodo imperiale; 3.2 - dalla Prima alla Seconda Restaurazione; 3.3 - dalla Monarchia di luglio alla Legge sulla separazione; 3.4 - le competenze - 4. Le bureau des cultes des départements du Bas-Rhin, du Haut-Rhin et de la Moselle: 4.1 - la specificità dell’Alsazia-Mosella; 4.2 - le origini del bureau; 4.3 - le competenze - 5. Il conseiller pour les affaires religieuses: 5.1 - le origini; 5.2 - la posizione fuori dagli schemi; 5.3 - le competenze – 6. Conclusioni.  Abstract:The administration of cults in FranceThe expression “Administration of cults” born in France in the 19th century, when the 1801 Conordat made the cults into a public service and the cult's clerics a corp of nominated functionaries. Thus administration referred precisely to that branch of the civil service which under the flourishing Concordat concerned itself with the problems of claims from and requirements of the religious cults in French territories. Our paper means to trace France's administration of cults from its beginnings to its precise modern competences and functions. We wish to show how this administrative structure has been and still is an important apparatus for interpretation and even for 'liberal administration' of the Law as regards the separation of State and Church and the very concept of laïcité.Key words: France, administration, cults, laïcité